Eclipse (2016), volume 4 ebook - Kaplan, Zack (Eclipse (2016), 2019)
In a world where sunlight is deadly, the final confrontation plays out between the corrupt solar tycoons and those mysterious individuals immune to the sun's rays. And caught in the middle are ordinary heroesa solar heiress turned rebel and a disillusioned former herowho must rescue all of Manhattan from a villainous plot to destroy the solar power that protects the city. Collects ECLIPSE #13-16. Author: Zack Kaplan. Illustrator: Giovanni Timpano . 2019 Top Cow Productions, Inc.